Gremmeniella abietina-epidemin 2001 - Grönkvist Wichmann, Lo (2011)
The fungus Gremmeniella abietina causes damage to conifers that can lead to tree death. In 1999 and 2001 the pathogen caused severe attacks in Sweden, where about 500 000 ha of pine forest were affected. Trees of all ages were attacked, but mainly forests between 30-60 years that were ready for their first commercial thinning. After recommendations from the forest agency, sanitary fellings were made to trees that had more needle loss than 85%, a total of about 50 000 ha. Economic losses have been estimated to more than one billion SEK.